Apoptosis of Human Islet Cells by Cytokines - Kim, Sun-Shin; Kim, Kyoung-Ah; Suk, Kyoung-Ho; Kim, Yun-Hee; Oh, Seung-Hoon; Lee, Moon-Kyu; Kim, Kwang-Won; Lee, Myung-Shik (Immune network, 2012)
FasL, perforin, TNFα, IL-1 and NO have been considered as effector molecule(s) leading to β-cell death in autoimmune diabetes. However, the real culprit(s) of β-cell destruction have long been elusive despite intense investigation. Previously we have suggested IFNγ/TNFα synergism as the final effector molecules in autoimmune diabetes of NOD mice. A combination of IFNγ and TNFα but neither cytokine alone, induced classical caspase-dependent apoptosis in murine insulinoma and pancreatic islet cells. IFNγ treatment conferred susceptibility to TNFα-induced apoptosis on otherwise resistant murine insulinoma cells by STAT1 activation followed by IRF-1 induction. Here we report that IFNγ/TNFα synergism induces apoptosis of human pancreatic islet cells. We also observed STAT1 activation followed by IRF-1 induction by IFNγ treatment in human islet cells. Taken together, we suggest that IFNγ/TNFα synergism could be involved in human islet cell death in type 1 diabetes, similar to murine type 1 diabetes.